2009
DOI: 10.1016/j.biopsych.2008.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Function and 5-HTT Gene Variants in Adolescent Anxiety and Major Depressive Disorder

Abstract: Background-Associations between a functional polymorphism in the serotonin transporter gene and amygdala activation have been found in healthy, depressed, and anxious adults. This study explored these gene-brain associations in adolescents by examining predictive effects of serotonin transporter gene variants (S and L G allele carriers vs. L A allele homozygotes) and their interaction with diagnosis (healthy vs. patients) on amygdala responses to emotional faces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
90
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(107 citation statements)
references
References 50 publications
(59 reference statements)
15
90
1
1
Order By: Relevance
“…The literature also shows high rates of comorbidity between major depressive disorder and anxiety disorders. Some authors recognize anxiety as an axial symptom in major depression, and have found evidence of the relationship between the polymorphism evaluated in this study and anxious symptoms, the activity of the amygdala and the anxiety response (33)(34)(35)(36). In addition, some authors have pointed out that the comorbid anxiety disorders of major depression increase implicit suicide risk (37).…”
Section: Discussionsupporting
confidence: 53%
“…The literature also shows high rates of comorbidity between major depressive disorder and anxiety disorders. Some authors recognize anxiety as an axial symptom in major depression, and have found evidence of the relationship between the polymorphism evaluated in this study and anxious symptoms, the activity of the amygdala and the anxiety response (33)(34)(35)(36). In addition, some authors have pointed out that the comorbid anxiety disorders of major depression increase implicit suicide risk (37).…”
Section: Discussionsupporting
confidence: 53%
“…Consistent with the 5-HT alterations and various subtle neurodevelopmental alterations observed in SLC6A4 knockout mice [34][35][36], carriers of the s allele showed amygdala hyper-reactivity [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] upon exposure to emotional stimuli as well as reduced functional connectivity between the amygdala and the perigenual cingulate cortex [37]. They also showed decreased grey matter volume in limbic structures (e.g.…”
Section: (B) Slc6a4 and Integrity Of The Brainmentioning
confidence: 77%
“…Age Neuroimaging studies conducted in children and adolescents with MDD also show heightened activation in the amygdala 56,60,74 and OFC 74 in response to emotional facial expressions (for conflicting findings, see Thomas and colleagues 42 ).…”
Section: 57mentioning
confidence: 99%
“…Accordingly, a number of studies reviewed here have excluded patients with comorbid psychiatric diagnoses, including anxiety disorders. 43 60 carried out subanalyses to investigate the impact of comorbidity status, finding no significant differences. Two studies 42,56 directly compared neural activity in patients with a primary diagnosis of an anxiety disorder and patients with a primary diagnosis of MDD.…”
Section: Comorbiditymentioning
confidence: 99%
See 1 more Smart Citation